A Efl Teachers’ Pedagogical Challenges In Online Teaching During Pandemic Period : (A Case Study at SMK NURUL HUDA BAROS) - Eva Alawiyah; Abdul Muin; Tri Ilma Septiana (CV. Era Digital Nusantara, 2024)
This study aims to find out the pedagogical challenges faced by EFL Teacher in online teaching and how teacher overcome the pedagogical challenges dealing with online teaching. This study used case study with data collection technique through observations, interviews and document analysis. Based on the research finding, the results showed that, there are four challenges that faced by English teacher such as: (1) The difficulty in designing and delivering material (2) Teacher have difficulty in controlling the intereaction with student (3) Teacher need more time in preparing learning content (4) Teacher have difficulty in giving assignments and assessment for students. To overcome these challenge, the finding shows some solution by doing: (1) Shared the material before learning begin (2) build a good communication with students in online learning process (3) give extra point (4) Using learning media in delivering the material.